Evaluation of the efficacy of carbamazepine and gabapentin in the management of trigeminal neuralgia: A clinical study - Bhawandeep Kaur (Journal of Indian Academy of Oral Medicine and Radiology, 2018)
Background: Trigeminal neuralgia (TN) is a syndrome of unilateral, paroxysmal, stabbing facial pain, originating from the trigeminal nerve. Carbamazepine still remains as the gold standard drug in terms of efficacy in TN. Over the time, several other drugs are also used as alternatives for TN such as oxcarbazepine, baclofen, lamotrigine, levetiracetam, gabapentin, valproate, botulinum toxin A injection. Objective: To Evaluate the efficacy of Carbamazepine and Gabapentin in the management of Trigeminal Neuralgia. Materials and Methods: A total of 42 patients with a mean age of 52.78 years included in the study were randomly divided into two groups A and B and were given the tablets of carbamazepine in the dose range of 400mg to 1200 mg and gabapentin in the dose range of 600mg to 1800mg and recalled after 3rd day, 15th day, 1 month and 3 month period to evaluate the response to the drugs. The collected data was subjected to statistical analysis. Results: The therapeutic effectiveness of carbamazepine recorded as good response in 52.38% of patients of group A after 72 hours of recall while 28.57% patients had an average response and 19% patients had not relieved off pain attacks at the dose of 400mg of carbamazepine. The therapeutic effectiveness of gabapentin recorded as good response in 52.38% of group B patients after 72 hours of recall while 42.8% patients had an average response at the dose of 600mg of gabapentin. Conclusion: The study suggests that gabapentin can be effective as first or second line treatment of trigeminal neuralgia, even in cases resistant to traditional treatment modalities.